Developing Internal Capabilities of the Ministry of Finance - Rita Laba’ada; Windriawati Sullah; Sartina R. Male (Proceeding of The International Conference on Business and Economics, 2023)
Capacity, authority, and competency are necessary for internal auditors to perform supervisory responsibilities. Six components make up the Internal Audit Capability Model, which is used to gauge capability. The goal of this study is to ascertain the measures taken to enhance the Ministry of Finance's Inspectorate General's capacity to attain level 3 Government Internal Audit Apparatus competency. Excellent governance, risk management, and control are demonstrated by the organization's Level 3 internal audit capacity. Consequently, internal auditors play a critical role as strategic collaborators. The Ministry of Finance's Inspector General then assesses and examines the issue. Through case studies, qualitative research was carried out for this subject. Interviews and document reviews were used to gather data.l. Nevertheless, several elements of the Internal Audit Capability Model at level 2 still rely on the outcomes of self-evaluation, while other elements do not fully satisfy the requirements for level 3. This necessitates the adoption of thorough Corporate Risk Management as well as evaluation for three years in a row. Thus, enterprise risk management is a useful tool for internal auditors' supervisory duties. The research findings may also be helpful to other establishments aiming to attain level 3 internal audit proficiency.